Righting The Wrongs Of The Past: Corridors Of Freedom As A Pathway To Inclusive Development - Masingi, Carol (Department of Sociology, 2020)
South African cities are still largely unequal where the urban poor’s right to the city is not adequately addressed. As a result of the legacy of apartheid and the various housing policies that have been adopted to address housing segregation, Johannesburg remains spatially fragmented with the urban poor remaining isolated in the periphery of the city far from places of employment and opportunity. With the decentralization and deindustrialization of employment, commuting for the urban poor has become more time consuming and costly with an average monthly commute costing R1 500.00. The City of Johannesburg has committed to tackling these structural and spatial inequalities that exist in Johannesburg through its flagship programme called Corridors of Freedom. Corridors of Freedom aims to transform the spatial inequalities in Johannesburg through the creation of geographies of inclusion using transit oriented development (TOD). This is through investing in public transport with the development of the Rea Vaya Bus Rapid Transit System (BRT) and inclusionary housing as the backbone to eradicate spatial. Corridors of Freedom aims to address housing segregation through the extension of the Rea Vaya BRT system in peripheral townships and through inclusionary housing provision to promote inclusive development in Johannesburg. This study will evaluate whether Corridors of Freedom and its associated developments have the potential to improve the lives of potential beneficiaries of two townships, Kagiso in the West Rand and Soweto. The study seeks to understand how the presence of the Rea Vaya BRT system can assist the urban poor’s access to the city and places of employment and opportunity. A comparison is made between Soweto residents who directly benefit from using the Rea Vaya buses and the Kagiso residents who do not have access to the Rea Vaya buses. Several stakeholders were interviewed including both the residents of Kagiso and Soweto. It was concluded that the Rea Vaya BRT system is a poverty-reduction strategy for the urban poor and an attempt from the City of Johannesburg to correct the existing spatial inequalities.The Rea Vaya Bus Rapid Transit system along with well-located social housing is an important step towards addressing inclusivity and bringing people close to places of employment and opportunity.